The effects of hot air-dried and freeze-dried treatments on Shiitake mushroom (Lentinula edodes): A review / Nor Syafini Roslan and Naemaa Mohamad - Roslan, Nor Syafini; Mohamad, Naemaa (2021)
The total world production of mushrooms were 11 million metric tons and 73.9% of the production was from Asian region as they are being consumed throughout the world for their specific aroma, texture and taste. During storage and transportation fresh shiitake mushrooms are prone to texture softening thus declining its quality as fresh shiitake have a high-metabolic rate after plucking and have high water content. Thus, two out of the various drying techniques which are hot air-drying (HAD) and freeze-drying (FD) that are being used as a preservation method for shiitake mushrooms were reviewed in this paper. HAD provided a simple drying mechanism to dry food products but the prolonged time and high drying temperature were the major drawbacks as it produced an extensive deterioration of final product structure. While, FD is able to produce a final dried product resembling the fresh product state but has a higher production cost compared to HAD. In this review, the comparison between HAD and FD on the qualities of shiitake mushrooms were discussed. Based on the literature, there is a lack of research being done that describes the qualities such as physicochemical properties, sensorial, nutritional and microbial safety of HAD and FD on shiitake mushrooms. Overall, HAD and FD have their own advantages and limitations, further research should be done to compare and optimize HAD and FD in order to produce good qualities of dried shiitake mushrooms.